Development of advanced batteries and their materials - Ozawa, Takeo (Bulletin of the Japan Institute of Metals, 1987)
The Japan national plan and the present status of the research and development of advanced new batteries are presented on the subjects of new types of batteries, systems, new battery storage system for 1 kW power level and the total system from 1980-1990. It is indicated that new batteries of 10 kW were scheduled for testing in 1986. Various types of battery principles, their characteristics and the future task are introduced and compared with each other. New and conventional batteries discussed are Na--S, Zn--Cl, zinc-bromide, redox type battery (Cr--Fe) and Pb battery. 13 ref.--D.W.M.